2005
DOI: 10.1074/jbc.m410537200
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucuronic Acid:Anthocyanin Glucuronosyltransferase from Red Daisy (Bellis perennis) Flowers

Abstract: In contrast to the wealth of biochemical and genetic information on vertebrate glucuronosyltransferases (UGATs), only limited information is available on the role and phylogenetics of plant UGATs. Here we report on the purification, characterization, and cDNA cloning of a novel UGAT involved in the biosynthesis of flower pigments in the red daisy (Bellis perennis). The purified enzyme, BpUGAT, was a soluble monomeric enzyme with a molecular mass of 54 kDa and catalyzed the regiospecific transfer of a glucurono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Each of these Vv GT genes was predicted to have a single intron. Phylogenetic analysis revealed that each of these genes is related to the GT1 family phylogenetic cluster (cluster I) of flavonoid 3-O-glycosyltransferases, as expected (Vogt and Jones, 2000;Sawada et al, 2005;Noguchi et al, 2007). Moreover, these genes formed a subcluster that was distinct from the Vv GT1-related subcluster ( Figure 1B).…”
Section: Screening Of V Vinifera Flavonoid-3-o-glycosyltransferase Gmentioning
confidence: 97%
See 3 more Smart Citations
“…Each of these Vv GT genes was predicted to have a single intron. Phylogenetic analysis revealed that each of these genes is related to the GT1 family phylogenetic cluster (cluster I) of flavonoid 3-O-glycosyltransferases, as expected (Vogt and Jones, 2000;Sawada et al, 2005;Noguchi et al, 2007). Moreover, these genes formed a subcluster that was distinct from the Vv GT1-related subcluster ( Figure 1B).…”
Section: Screening Of V Vinifera Flavonoid-3-o-glycosyltransferase Gmentioning
confidence: 97%
“…Previous studies of two GATs, Bp UGAT (UGT94B1) of the red daisy flower (Bellis perennis) (Sawada et al, 2005;Osmani et al, 2008) and Pf F7GAT (UGT88D7) of Perilla frutescens (Noguchi et al, 2009a), showed that Arg-25 in Bp UGAT and Arg-350 in Pf F7GAT play an important role in recognition of UDP-GA. These results suggest plasticity of the mechanisms that alter the sugar donor specificity of UGTs.…”
Section: Identification Of a Residue That Critically Determines The Smentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the a-D-glucuronic acid units can be attached to the O-2 position of the xylan backbone as side groups [2]. Additionally, Sawada et al [3] demonstrated that BpUGAT (Bellis perennis glucurowww.cell-research.com | Cell Research Ai-Min Wu et al 175 npg nosyltransferase) catalyzes the regiospecific transfer of GlcA to the 2-hydroxyl group of the 3-glucosyl moiety of the substrate anthocyanidin. These results suggest that the UGTs may be important in regulation of differentiation and secondary metabolism [4][5][6].…”
Section: Introductionmentioning
confidence: 99%